IDENTIFICATION OF BANKING RISKS AND THEIR IMPACT ON FINANCIAL STABILITY - Lutsyk, Mariia; Solovarov, Andrii; Paliukh, Anton (Socio-economic relations in the digital society, 2022)
The article is devoted to deepening the theoretical and methodological foundations of the study of banking risks and their impact on financial stability. Based on the generalization of the results of scientific research, the essence of the concepts "financial stability", "banking risks" was specified. Methodological approaches to the identification and classification of banking risks are substantiated. The study made it possible to distinguish between the concepts of financial stability and the financial fortitude of the banking system. It is emphasized that financial stability is a dynamic characteristic of the banking system, while financial fortitude reflects its current, static state. In the article, the types of risks inherent in the banking system are specified, and the classification features that allowed identification of the main risks that have the greatest impact on financial stability are identified. It has been established that in modern conditions, a significant threat to financial stability can be posed by a sharp deterioration of conjuncture in the global financial and/or commodity markets, which is transmitted to the banking system; "overheating" of one of the segments of the domestic financial market; a speculative attack on the national currency for keeping its exchange rate effectively pegged to the US dollar and deterioration of the trade balance; the crisis of the public finances, etc.